ECONOMIC CONSEQUENCES OF CORRUPTION IN TRANSITION ECONOMIES - Linhartová, Veronika; Owusu, Evans (IIOAB, 2019)
Corruption is one of the perturbing issues that has manifested itself in almost every part of the globe. Its impact through direct and indirect means does not only affect a person but the entire population which can further extend to generations. Many scholars in light of its undesirable effect have undertaken studies to create awareness of the degree of the impact corruption is causing or can cause, both socially and economically. However, countries with transition economies have been vulnerable to corruption due to factors like privatization and restitution during the transition process. As such, Czech Republic, Hungary, Slovakia and Poland which are European countries with transition economies were studied with regards to the economic consequence of corruption. The goal of this paper is to assess whether the level of corruption differs significantly among the four countries and to ascertain the effect of corruption on economic growth of the selected countries. A quantitative research method was employed in the research design and the analyses of this paper. To achieve the first specific objective, that is, to assess whether the level of corruption differs significantly among the four countries, the Kruskal Wallis test was used. Also, to achieve the second specific objective, the data for the socio-economic variables were visualized using descriptive graphs and then correlation and multiple linear regression were used. The analyses revealed that the level of corruption was significantly different among the countries for the selected period of years 2008-2017. The economic consequences were evident in the level of Foreign Direct Investment, Gross National Expenditure and GDP growth. As clearly highlighted in the analysis, corruption has a tremendous devastating effect on socio-economic fortunes of a countries. Arguably, it can reasonably be concluded that the level of developments of certain countries could have been much better if corruption was reduced.
Ekonomické důsledky korupce v tranzitivních ekonomikách
Keywords: corruption; transition economies; public officials; transmission channels; economic impact; private gain.; korupce; tranzitivní ekonomiky; úředníci; transmisní kanály; ekonomický důsledek; osobní prospěch.